The Effect Of Organizational Climate On The Performance Of Employees In The General Secretariat Of Lattakia Governorate - ناصر فداء; مجارسه حازم (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The research aims to study the impact of the organizational climate in its dimensions (organizational structure, leadership, incentives, participation in decision-making, training, technology) on the performance of workers in the General Secretariat of Lattakia Governorate. In order to achieve this goal, the researcher designed a questionnaire and distributed it to a random sample of the study population. The researcher adopted the descriptive analytical approach and used the statistical analysis program (SPSS.24) to analyze the questionnaire. The researcher find out that there is a statistically significant effect of the organizational climate dimensions (organizational structure, leadership, incentives, training) on ​​the performance of employees in the General Secretariat of Lattakia Governorate, while there is no statistically significant effect of the two dimensions (participation in decision-making, technology) on the performance of employees . There are no statistically significant differences between the employees ’answers about the questionnaire axis due to the variables (gender, age, educational qualification, experience), except for the presence of statistically significant differences between employees’ answers about (leadership, training, employee performance) attributed to the job title. The researcher finished his study with several recommendations that would enhance the organizational climate in a way that helps improve the performance of employees.